2019
DOI: 10.1371/journal.pone.0217572
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte counts may predict a good response to mesenchymal stromal cells therapy in graft versus host disease patients

Abstract: Steroid-resistant GvHD is one of the most significant causes of mortality following allogeneic Hematopoietic Stem Cell Transplantation (HSCT). Treatment with mesenchymal stromal cells (MSC) seems to be a promising solution, however the results from clinical studies are still equivocal. Better selection of candidate patients and improving monitoring of patients following MSC administration can increase treatment effectiveness. In order to determine which characteristics can be used to predict a good response an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Another approach is to monitor cellular pathways that have been reported to be mediators of MSC immunosuppression. Hinden et al [ 72 ] reported that the number of lymphocytes, especially T cells and NK cells, was significantly higher in responders than in non-responders before MSC administration. The more inflammatory milieu of responders is conducive to MSC “licensing” and thus is beneficial for MSCs to play an immunomodulatory role [ 73 ].…”
Section: Reasons For Erratic Results Of Clinical Trialsmentioning
confidence: 99%
“…Another approach is to monitor cellular pathways that have been reported to be mediators of MSC immunosuppression. Hinden et al [ 72 ] reported that the number of lymphocytes, especially T cells and NK cells, was significantly higher in responders than in non-responders before MSC administration. The more inflammatory milieu of responders is conducive to MSC “licensing” and thus is beneficial for MSCs to play an immunomodulatory role [ 73 ].…”
Section: Reasons For Erratic Results Of Clinical Trialsmentioning
confidence: 99%
“…MSCs transiently activate T cells to preserve the antiapoptotic function ( 44 ). For example, higher lymphocyte counts were more efficient in activating MSCs in the treatment of graft vs. host disease ( 45 ). A previous study showed that that hUC-MSCs recruited the regulatory T cells in the damaged lung ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, interactions between MSCs and immune cells are of utmost importance in dictating response to MSC therapy. A small study investigating differences between responders and non-responders to MSC therapy for GvHD found that patients with high peripheral blood lymphocyte counts (CD3 + T cells and CD56 + NK cells) before MSC therapy responded better ( 73 ). In addition strong cytotoxicity towards MSCs by peripheral blood mononuclear cells (PBMCs) from GvHD patients ( 74 ) was associated with a better response to MSC therapy.…”
Section: Impact Of Disease Microenvironment On Msc Efficacymentioning
confidence: 99%